Intercultural Spacing: The Construction of Symbolic Territory and Its Ethical-Aesthetic Cartographies as Visual Memory of Belonging Processes in Lima Metropolitana - Villavicencio Monti, Karla (2020)
It is attempted to show the possibilities of symbolic representation under an interdisciplinary approach, from Art and Architecture applied to the peripheral problems of the environment and to their reconstruction from the territory, evidencing a symbolic heritage based on the production of cartographies that show ethical-aesthetic values as a possibility of representation of the visual memory contained in the belonging processes occurring in the city of Metropolitan Lima.How could we view these reconstruction processes made by our memory around the spaces where we live and participate or how could migration paths be evidenced from that perspective? A methodology is proposed based on three phases of recognition of a personal route of rearrangement of individual history which starts from topographic knowledge of the territory in the reconstruction of personal experiences, to develop then cartographic sketches for the viewing of their implication in the reading of migration processes, as well as collective problems.This methodology will be explained through the development of three specific projects. Individual visual and installation artworks «De Reducto n. 2 a la Portada de Maravillas: Hacia el Descanso», «La Ruta de 50 Años» and Group Project «CO(HABITAR)».It can be recognized that the viewing of migration processes, from their symbolic aspects, represent diverse variants of recognition of the events experienced in the territory implying various layers of a reading that before being illustrative could be viewed through the processes of artistic expression, depending on the different origins of their participants and their experiences in the city. Those processes reconstruct the time lived as a cartographic set that can be viewed.